2019
DOI: 10.1111/agec.12502
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers’ preference for traits of chickens in rural Ethiopia

Abstract: Traditional poultry production plays an irreplaceable role in the sustenance of livelihoods in rural Ethiopia. Ironically, however, much has been done to replace indigenous poultry breeds with exotic genetic resources regardless of the importance producers and consumers attach to attributes of the resources. This study aims at informing policy to establish effective indigenous poultry breeding and conservation programs. Discrete choice experiment (DCE) was employed to generate data. Designing of the DCE involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
7
0
2
Order By: Relevance
“…Recently Ethiopian government exported exotic breed to improve their local chicken (Terfa et al 2019). This program might have been based on the report of (Wondmeneh et al 2016) who compared egg production between Horro improve breed of local chicken with modern commercial ISA Brown, crossbred of ISA Brown X Horro, and indigenous Ethiopian breed of chicken, showed that egg production recorded for 24 weeks of those evaluated breeds, were respectively 57,1% HH; 92,2% HH; 83% HH dan 27,1%.…”
Section: Average Egg Production (Aep)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Ethiopian government exported exotic breed to improve their local chicken (Terfa et al 2019). This program might have been based on the report of (Wondmeneh et al 2016) who compared egg production between Horro improve breed of local chicken with modern commercial ISA Brown, crossbred of ISA Brown X Horro, and indigenous Ethiopian breed of chicken, showed that egg production recorded for 24 weeks of those evaluated breeds, were respectively 57,1% HH; 92,2% HH; 83% HH dan 27,1%.…”
Section: Average Egg Production (Aep)mentioning
confidence: 99%
“…The improvement of the breed through selection is time-consuming which is resulting in more permanent product quality (Padhi 2016), whilst crossbreeding may increase productivity quickly, but it will deplete its original genetic resources very fast (Dessie et al 2011). Some developing countries like Ethiopia (Mengesha 2012;Hailu et al 2014;Gebremariam et al 2017;Terfa et al 2019), Kenya (Magothe et al 2015;Kamau et al 2019), Nigeria (Nwogwugwu et al 2018), Ghana (Osei-Amponsah et al 2015), India (Haunshi et al 2019), and Thailand (Suphawadee & Tuan 2016), have increased their local breeds of chicken either through selection or crossbreeding. Eventually in Indonesia, the work of improvement of local chicken breeds has been initiated as well (Sartika et al 2013;Iskandar & Sartika 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Perbaikan genetik dengan cara seleksi walaupun lama namun dapat menghasilkan kualitas produksi yang permanen (Padhi 2016), sedangkan perbaikan genetik dengan crossbreeding sangat cepat meningkatkan produktivitas namun seringkali menguras sumberdaya genetik aslinya (Dessie et al 2011). Beberapa negara berkembang di Afrika dan Asia telah melakukan peningkatan produktivitas ayam lokal baik melalui seleksi maupun crossbreeding seperti di Ethiopia (Mengesha 2012;Hailu et al 2014;Gebremariam et al 2017;Terfa et al 2019), di Kenya (Magothe et al 2015;Kamau et al 2019), di Nigeria (Nwogwugwu et al 2018), di Ghana (Amponsah et al 2015), di India (Haunshi et al 2019), di Thailand (Suphawadee & Tuan 2016) dan Indonesia (Sartika et al 2013;Iskandar & Sartika 2014).…”
Section: Pendahuluanunclassified
“…Milkias et al (2019) pada ayam lokal Ethiopia di Distrik Gena Bossa pada berbagai agroekosistem dataran rendah, sedang dan tinggi dengan pemeliharaan tradisional mendapatkan hasil produksi telur yang sangat rendah dibandingkan dengan penelitian ini yaitu 38,73; 40,45; 36,42 butir/ekor/tahun. Untuk meningkatkan produksi telur di Ethiopia, pemerintahnya mendatangkan breed exotic, untuk disilangkan dengan ayam lokal di Ethiopia (Terfa et al 2019). Hal tersebut telah dilakukan Wondmeneh et al (2016) yang melakukan evaluasi produksi telur improve breed ayam Horro, komersial breed ayam ISA Brown, crossbred (ISA Brown X Horro) dan ayam lokal asli Ethiopia mendapatkan produksi telur hen house selama 6 bulan untuk masing-masing breed tersebut sebesar 57,1%; 92,2%; 83% dan 27,1%.…”
Section: Produksi Telurunclassified
“…Native chicken breeds in traditional extensive production systems are integral part of the poultry production in developing countries (Ghayas et al, 2020). These chickens are famous for better adaptability to the local environment (Batool et al, 2018) and their perpetuate role in breaking the vicious cycles of nutritional scarcities in developing countries (Terfa et al, 2019). However, due to unplanned and haphazard crossing in village farming systems, the traits of economic importance in these birds are not feasible for enough profit generation.…”
Section: Introductionmentioning
confidence: 99%